2013
DOI: 10.1016/j.cej.2013.05.071
|View full text |Cite
|
Sign up to set email alerts
|

Detachment characteristics of a mixed culture biofilm using particle size analysis

Abstract: Detachment is a critically important aspect of biofilm processes; it impacts not only on the characteristics of the biofilm itself but also has general implications for the dissemination of pathogenic bacteria and the operation of biofilm reactors. The mechanisms of biofilm detachment are of fundamental importance in the analysis of biofilm processes. However the complexity of biofilm detachment creates difficulties in performing and analyzing experiments. It is necessary to identify if, under steady condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
1
11
1
Order By: Relevance
“…All these observations are fairly consistent with experimental work. For example,Walter et al [ 51 ] have demonstrated that when a shear flow is applied to a mature biofilm, the number of erosion events suddenly increases and then gradually decreases over the time. Fig 11(C) shows the frequency distribution of the volume of the detached clusters from time T ** = 0 to 1.3×10 5 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these observations are fairly consistent with experimental work. For example,Walter et al [ 51 ] have demonstrated that when a shear flow is applied to a mature biofilm, the number of erosion events suddenly increases and then gradually decreases over the time. Fig 11(C) shows the frequency distribution of the volume of the detached clusters from time T ** = 0 to 1.3×10 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Even though larger clusters are produced at higher shear rates due to streamer detachment, that frequency is smaller. Walter et al [ 51 ] also reported that the mean cluster size for erosion would decrease as shear rate increases. As expected, there is a monotonically increasing relationship between the average detachment rate and shear rate ( Fig 12C ).…”
Section: Resultsmentioning
confidence: 99%
“…Turbulence generated during peak flow results in mixing, an increase in oxygenation, bubble generation, and shear stress, which increases detachment rates from sediment and is dependent on bacterial shape and strain, and biofilm cohesive strength (Gomez-Suarez et al, 2001; Young, 2006; Lemos et al, 2014; Figure 1D). The release/resuspension of bacteria from biofilms within sediments is dependent on the combination of physicochemical forcing (Walter et al, 2013) and biotic factors, such as grazing and quorum sensing (Costerton et al, 1995; Kim et al, 2016) which could impact particulate loading to the water column (Figure 1E). …”
Section: Sediments As a Sink/source Of Fecal Bacteria And Viruses?mentioning
confidence: 99%
“…Biofilms are microorganisms in which cells attach and grow on a surface, and these cells are embedded in an extracellular polymeric matrix [1]. They have a significant impact on human health, industry, and the environment since they are ubiquitous [2].…”
Section: Introductionmentioning
confidence: 99%